Analisis Kebijakan Kesehatan Mendorong Partisipasi Masyarakat dalam Program Pencegahan Penyakit - Ana Nurjanah; Salsabila Zahri Sativa; Aprillia Dwi Astuti; Suci Ramadhani Rangkuti; Nailah Nafisah; Nabila Fitri; Risna Utami; Irfan Sazali Nasution (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
This article analyzes health policies aimed at promoting community participation in disease prevention programs. The study aims to investigate the effectiveness of current policies in fostering active involvement of communities in disease prevention efforts. Methodologically, a comprehensive review of existing health policies and their implementation strategies is conducted, focusing on case studies and empirical data from various regions. The results highlight the critical role of community engagement strategies in enhancing the effectiveness and sustainability of disease prevention initiatives. The analysis underscores the importance of tailored policy interventions that empower communities through education, resources, and participatory decision-making processes, thereby strengthening public health outcomes and promoting a culture of proactive health management.